Exploring nitrogen limitation for historical and modern soybean genotypes - Ortez, O.A. (2018)
The United States (USA) and Argentina (ARG) account for over 50% of the global soybean [Glycine max (L.) Merr.] production. Soybean N demand is partially met (50–60%) by the biological nitrogen fixation (BNF) process; however, an unanswered scientific knowledge gap exists on the ability of the BNF process to fulfill soybean N demand at varying yield levels. The overall objective of this study is to explore the potential N limitation using different N strategies for historical and modern soybean genotypes. Four field experiments were conducted during 2016 and 2017 growing seasons in Kansas (USA) and Santa Fe (ARG). Twenty-one historical and modern soybean genotypes released from the 1980s to 2010s were tested under three N treatments: (i) control, without N application (Zero-N); (ii) 56 kg N ha–1 applied at R3-R4 growth stages (Late-N); and (iii) 670 kg ha–1 equally split at planting, R1, and R3–R4 growth stages (Full-N). Historical soybean yield gains, from the 1980s to 2010s, were 29% in the USA and 21% in ARG. Following the yield trend, seed N content increased for modern genotypes in parallel to the reduction on seed protein concentration. Regarding N treatments, Full-N produced 12% yield increase in the USA and 4% in ARG. Yield improvement was mainly related to increases in aboveground biomass, seed number (genotype effect), and to a lesser extent, to seed weight (N effect). This study suggests a potential N limitation for soybean, although there are still questions about the way in which N must be provided to the plant.